Effect of carbon black loading on the mechanical properties of rubber vulcanizates - Mohd Faisal, Ahmad Shafawi (2010)
The effects of filler loading on the tensile and elongation at break of SMR 10 using a sulphur vulcanization system was studied. Carbon black (N220) was used as the fillers and the loading range was from 10 to 40 phr. Two Roll Mill (Model LS-22005) and 25 Ton Hot Cold Molding Press (Model LS22025) used for mixing and molding press. Both equipments were supplied by Lotus Scientific. Tensile and elongation at break were determined using a Universal Testing Machine (Model 133004600771) operating at 20 mm/min. Results show that, elongation at break decreases, but tensile strength, increase with filler loading. This observation is attributed to the rubber–filler interphaseinteraction of carbon black and rubber.